Kw = [H+][OH-]

 

 

 

LnKw = 148.96502 - 13847.26/T - 23.6521*log(T) + (118.67/T - 5.977 + 1.0495*log(T))*S^0.5 - 0.01615*S : Kw = exp(LnKwP) : [H+] = [H+]T

K0 = [H2CO3*]/f(CO2)

LnK0 = 9345.17/T - 60.2409 + 23.3585*log(T/100) + S*(0.023517 - 0.00023656*T + 0.0047036*(T/100)^2) : K0 = exp(LnK0)

f(CO2) if the fugacity of CO2, which is numerically very similar to CO2 partial pressure in matm and therefore corresponding to ppmCO2 in dry air by the Dalton law. For further insight see the topic here.

K1 = [HCO3-][H+]/[H2CO3*]

LnK1 = 2.83655 - 2307.1266/T - 1.5529413*log(T) - (4.0484/T + 0.20760841)*S^0.5 + 0.08468345*S - 0.00654208*S^1.5 + log(1 - 0.001005*S):K1 = exp(LnK1) : [H+] = [H+]T

K2 = [CO3--][H+]/[HCO3-]

LnK2 = -9.226508 - 3351.6106/T - 0.2005743*log(T) - (23.9722/T + 0.106901773)*S^0.5 + 0.1130822*S - 0.00846934*S^1.5 + log(1 - 0.001005*S):K2 = exp(LnK2) : [H+] = [H+]T

Ksp(cal) = [Ca++][CO3--]

LogKspCal = -171.9065 - 0.077993*T + 2839.319/T + 71.595*log(T)/a1 + (-0.77712 + 0.0028426*T + 178.34/T)*S^0.5 - 0.07711*S + 0.0041249*S^1.5                     LnKspCal = LogKspCal*log(10)

Ksp(arg) = [Ca++][CO3--]

LogKspAra = -171.945 - 0.077993*T + 2903.293/T + 71.595*log(T)/a1 + (-0.068393 + 0.0017276*T + 88.135/T)*S^0.5 - 0.10018*S + 0.0059415*S^1.5
LnKspAra = LogKspAra*log(10)

K7 = [Ca(OH)+]/([Ca++][OH-])

DG = -7576 Joule:K7 = exp(-1*deltaG/(R*T))

 

K8 = [Mg(OH)+]/([Mg++][OH-])

DG = -14656 Joule:K8 = exp(-1*deltaG/(R*T))

 

KB = [H+][B(OH)4-]/[B(OH)3]

LnKB = (-8966.9 - 2890.53*S^0.5 - 77.942*S + 1.728*S^1.5 - 0.0996*S^2)/T + 148.0248 + 137.1942*S^0.5 + 1.62142*S - (24.4344 + 25.085*S^0.5 + 0.2474*S)*log(T) + 0.053105*S^0.5*T : KB = exp(LnKB) : [H+] = [H+]T

HSO4- == H+ + SO4--

KS = [H+][SO4--]/[HSO4-]

where I (ionic strenght) = 19.924*S/(1000 - 1.005*S)

[H+]is the [H+] free concentration

HF  ==  H+  +  F-

KF = [H+][F-]/[HF]

where ST (total concentration of sulphate) = 0.02824*S/35 : [H+] = [H+]T

 

H3PO4  ==  H+  +  H2PO4-

K1P = [H+][H2PO4-]/[H3PO4]

 

H2PO4-  ==  H+  +  HPO4--

K2P = [H+][HPO4--]/[H2PO4-]

 

HPO4--  ==  H+  +  PO4---

K3P = [H+][PO4---]/[HPO4--]

 

Si(OH)4  ==  H+  +  H3SiO4-

KSi = [H+][H3SiO4-]/[Si(OH)4]

For all the expression : [H+] = [H+]T